Purchasing behavior in rural areas for food products during the COVID-19 pandemic - Pappalardo, Gioacchino; Selvaggi, Roberta; Pittalà, Michela; Bellia, Claudio (Frontiers in Sustainable Food Systems, 2022)
Introduction Most previous studies have investigated consumer purchasing behavior for food products in urban areas during the COVID-19 pandemic. In contrast, the present study is one of the very few to investigate consumer purchasing behavior for food products within rural areas. Methods To this end, research was conducted in Sicily taking as a case study a rural municipality whose population was subjected to a lockdown regime to contain the spread of the virus. The choice of carrying out the research in a rural rather than an urban area contributed to the emergence of new aspects concerning consumer behavior in rural areas during the COVID-19 emergency. Results and discussion The research reveals that the amount of money spent on food purchases, as well as the amount of food purchased, increased during the lockdown. In general, the research shows that COVID-19 impacted the purchasing behavior of consumers in rural areas even though they showed a high resilience and adaptation to the health emergency situation caused by the pandemic.